Pelatihan dan Sosialisasi Automated Trading Systems & Autopilot Manual Trading - Salam, Abdus; Wani, Cut Eva; Nasir; Farnita, Irma; Ismail; Alfina; Imilda (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Automated Trading Systems & Autopilot Manual Trading training for 6 days on 10-15 January 2023 provides an understanding of the concepts and workings of ATS and AMT as well as risk management in trading. This training is expected to make participants more independent in trading and able to maximize the use of ATS and AMT to gain profits in their investments. In addition, this training is expected to make a positive contribution in increasing financial literacy and investment in society. However, this needs to be done in a structured and comprehensive manner so that capital market participants understand the potential risks that may arise when using Automated Trading Systems and Autopilot Manual Trading in their investment activities. The recommendation that can be made is to hold regular training and outreach, both by regulators, securities companies, and capital market associations. With effective training and outreach as well as strict supervision, it is hoped that capital market players will be able to optimize their investment potential by avoiding unwanted risks. This training can also help increase awareness and understanding of sharia compliance in investing in the Indonesian sharia capital market.